THE FINANCIAL PERFORMANCE OF BANK BPD DIY PRE AND POST COVID-19 PANDEMIC - Bahri Bahri; Ilmardani Rince Ramli; Fikri Alamsyah (Kesatuan Press, 2022)
The outbreak of Covid-19 2019 had an impact on the decline in the economy of the Special Region of Yogyakarta and the financial performance of Bank BPD DIY. This study aims to analyze differences in the performance of Financial Performance and ROA values ​​of Bank BPD DIY between 2019, 2020, and 2021. The research method uses the Independent Sample T-Test. The population and sample using monthly financial statements are 36 samples. The results of the study show that in 2019, 2020 and 2021. Bank BPD DIY assets have decreased. The results of the independent test of the t-test sample show that there are differences in the financial performance of Bank BPD DIY between 2019, 2020 and 2021.